PENGARUH TEKNOLOGI INFORMASI DAN KOMPETENSI TERHADAP KINERJA PENGELOLAAN KEUANGAN PADA PEGAWAI BAGIAN PENGELOLAAN KEUANGAN DI BADAN KEUANGAN DAN ASET DAERAH (BKAD) KABUPATEN PURWAKARTA - Yunita Resmi, Rita; Andriani, Ratih (Program Studi Manajemen Fakultas Ekonomika dan Bisnis Universitas Majalengka, 2024)
The purpose of this study is to find out and analyze the influence of information technology and competence on financial management performance at Badan Keuangan Dan Aset Daerah (BKAD) Purwakarta Regency. This study uses a quantitative descriptive research method with data types primary, namely a questionnaire using a Likert measurement scale. Sample determination techniques using a purposive sampling method in which the determination of samples is based on certain characteristics and characteristics based on the characteristics or nature of the population, there are 40 respondents. The study results show that information technology partially has a positive and significant effect on financial management performance. This is evidenced by the tcal value of 6.515 > ttable 2.026 and the result of the sig value is 0.000 < 0.05. Partially, the competition also has a positive and significant effect on financial management performance with a tcal value of 0.371 > ttable 2.026 and the result of a gis value of 0.000 < 0.05. And simultaneously it shows that information technology and competence have a positive effect and are significant on financial management performance. This is evidenced by the value of Fcal of 106.967, which is greater than the Ftable of